2016
DOI: 10.1128/genomea.00810-16
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Bacteriophage MA12, Which Infects both Campylobacter jejuni and Salmonella enterica Serovar Enteritidis

Abstract: Here, we announce the complete genome sequence of Salmonella enterica serovar Enteritidis (S. Enteritidis) bacteriophage MA12, a 41-Kb chromosome. The strain can infect both Campylobacter jejuni (C. jejuni) and S. Enteritidis and can be used in phage therapy experiments with poultry and poultry meat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…Henriques et al demonstrated that administrating phages through aerosol spray during the transfer of eggs from incubators to hatchers can be a cost-effective and efficient method to reduce the horizontal transmission of Salmonella in poultry [339]. Bacteriophage treatment is a novel strategy for providing prophylactic treatment against poultry pathogens including Salmonella [340]. It can be used safely without altering the gut microbiota [341].…”
Section: Bacteriophagesmentioning
confidence: 99%
“…Henriques et al demonstrated that administrating phages through aerosol spray during the transfer of eggs from incubators to hatchers can be a cost-effective and efficient method to reduce the horizontal transmission of Salmonella in poultry [339]. Bacteriophage treatment is a novel strategy for providing prophylactic treatment against poultry pathogens including Salmonella [340]. It can be used safely without altering the gut microbiota [341].…”
Section: Bacteriophagesmentioning
confidence: 99%
“…Other authors have announced the complete genome sequence of bacteriophage isolated from water by using Salmonella enterica subspecies enterica serovar Enteritidis (S. Enteritidis). The bacteriophage can infect both C. jejuni and S. Enteritidis and can be used in phage therapy in poultry and to improve the biosafety of poultry meat [46].…”
Section: Salmonellamentioning
confidence: 99%